PENINGKATAN KOMPETENSI MEKANIK BENGKEL SEPEDA MOTOR MELALUI PELATIHAN DAN SERTIFIKASI KENDARAAN LISTRIK DI SURAKARTA - Onery Andy Saputra; Sudiro; Arif Surono; Nita Enjellina; Arifin Oktabrian (LPPM STAI Muhammadiyah Probolinggo, 2025)
The development of electric vehicles in Indonesia requires the readiness of mechanics with specialized competencies in maintenance and repair. However, most motorcycle workshop mechanics in the Soloraya region still have limited knowledge and skills. This community service program aims to enhance the competence of mechanics through electric vehicle training and certification. The program was conducted at the Automotive Workshop of Politeknik Indonusa Surakarta in collaboration with Wuling Motor Indonesia, involving 20 participants from various motorcycle workshops. The training materials covered electric motor systems, batteries, battery management systems (BMS), and high-voltage occupational safety. The implementation methods included theoretical delivery, interactive discussions, and hands-on practice in electric vehicle maintenance and repair. The results indicated improved participants’ understanding, as shown by pre-test and post-test evaluations, and further reinforced by the awarding of competency certificates. This activity not only provided direct benefits for workshop mechanics but also supported the acceleration of battery-based electric vehicle implementation in line with government programs. Through this training, mechanics are expected to adapt to the development of automotive technology, enhance the competitiveness of local workshops, and contribute to sustainable transportation development in Indonesia.